Creating organizational soul : the source of positive change and transformation - Bellingham, Richard (HRD Press, 2009)
Does your organization have soul? Are you passionate about a higher purpose? Do you engage in meaningful dialogue? Are you caring and compassionate? Do you spend time reflecting on critical issues? People in soulful organizations are able to say they demonstrate these behaviors everyday. You can become one of those people by following the advice and guidance in this innovative book. Creating Organizational Soul makes a compelling case for the strong connection between organizational soul and productivity, innovation and results. The intent of the book is to get leaders to take a hard look at where they are and look for ways to get better. The author demonstrates how to create soul in business, social service agencies and education. Included are many examples of exemplary fast-growing companies, large companies, small businesses, not-for-profit organizations and universities that are stepping up and making a difference. You'll learn: The principles of a soulful organization; What a soulless organization looks like; The conditions necessary for creating organizational soul; Success stories of people who have created soul in their organizations; How to get people and organizations to do what they need to do to create organizational soul and achieve extraordinary results. You'll also get tools to help you measure the soul health and sickness of your organization, assess your leadership ability and measure soulful conditions. Of special interest to leaders are the conversation templates that can be used in goal-setting sessions, mid-year and end-of-year reviews with employees.